Modern Biotechnologies for Improving Quality Traits in Horticultural Crops: Subject Review - Obaid, Parwen Alaaldin (American Journal of Botany and Bioengineering, 2025)
Application of cutting-edge biotechnologies, particularly gene editing methodologies like CRISPR/Cas9, are offering tremendous opportunities to enhance the desirable traits of horticultural crops like tomato, strawberry and cucumber. This review summarizes the recent use of these technologies to develop flavor, disease resistance and nutritional quality of horticultural crops with a focus on field and applied trials in different agricultural settings. It also deals with the ethical and regulatory considerations surrounding the use of these tools in agriculture, and closes with recommendations to support scientific research anddecision-making in this sensitive area, integrated withan overview of thescientific developments that should be expected from the 2015–25. Over the past few years there have been significant advancements in the field of biotechnology and gene editing technology, in particular CRISPR/Cas9, have been considered extremely promising for the development of value-added traits in horticultural crops. It will be reviewed in this paper recent applications of this technology for the modification of traits of leading horticultural crops, such as tomato, strawberry, and cucumber, with the goal of improving tolerance to diseases resistance, sensory attributes, and tolerance to environmental stresses. The review also considers regulatory and ethical issues related to the application of the technologies in agriculture and gives recommendations for the sustainable use of the tools.